Comparison of the continuous model and the finite element model of the gantry crane carrying structure for modal analysis - Vasiljević, Rade (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: To study the adequacy of applying numerical methods in the modal analysis of complex carrying structures of cranes. Methods: Comparative application of the analytical method and the numerical method - FEM. Results: Some comparative values of the modal parameters were obtained both analytically and numerically for the derived solution of a gantry crane carrying structure. Conclusion: It is shown that the numerical method can give a reliable general quality estimate of the structural behaviour of a complex carrying structure from the aspect of modal analysis.